Role of Fdi on Economic Growth: The impact of FDI on economic growth: A quantitative analysis using econometric techniques (Journal of Advances and Scholarly Researches in Allied Education, 2012)
In order to assess the roleof FDI on economic growth, two models were used. The estimation results of thetwo models are supported and further analysed by using the relevant econometrictechniques viz. Coefficient of determination, standard error, f- ratio, t-statistics, D-W Statistics etc.